2017
DOI: 10.5539/gjhs.v9n11p61
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and (Ab)Use in Connection with Novel Psychoactive Substances: A Cross-Sectional Analysis of Iraqi Medical Students

Abstract: Background: The extent of (ab)use of the Novel Psychoactive substances has been thoroughly mapped in the developed world, particularly in the US, Canada, UK, Western Europe, Australia, and New Zealand. However, there are still untapped geographic locations particularly in the developing world including the Middle East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…Descriptions of the studies are reported in Table 2. Of the included studies, only four were alcohol specific [17][18][19][20]; two were about substance use [21,22] and two about health risk behaviours [23,24]; one each was primarily focused on mental health disorders [25], smoking [26], novel psychoactive drugs [27], risky driving [28], and sleep disorders [29]. No literature was found that related to preventative strategies in relation to alcohol.…”
Section: Research Topicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Descriptions of the studies are reported in Table 2. Of the included studies, only four were alcohol specific [17][18][19][20]; two were about substance use [21,22] and two about health risk behaviours [23,24]; one each was primarily focused on mental health disorders [25], smoking [26], novel psychoactive drugs [27], risky driving [28], and sleep disorders [29]. No literature was found that related to preventative strategies in relation to alcohol.…”
Section: Research Topicsmentioning
confidence: 99%
“…Only one study recruited a sample from more than one province [25]. Four studies recruited from Baghdad [19][20][21]27] and Erbil [17,22,23,28]. Two recruited students from Karbala [18,26].…”
Section: Study Settings and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations